INFLUENCE OF PRODUCT SPECIFICATIONS AND PRICES ON THE LAPTOP PURCHASE DECISION HEWLETT PACKARD (HP) BRAND (Case Study on Pegasus Computer Store Customers Tebing Tinggi) - Ketaren, Abednego (RADJA PUBLIKA, 2022)
This study aims to determine the effect of product specifications and prices on purchasing decisions for Hewlett Packard brand laptops (a case study on a Pegasus computer store customer at Cliff High). The independent variables of this study consist of product specifications and prices, while the dependent variable is purchasing decisions. The research was conducted on the customers of Pegasus Computer Tebing Tinggi shop. Data were analyzed using multiple linear regression analysis method. The results of this study show. (1) Product specifications have an effect on purchasing decisions, (2) price has no significant effect on purchasing decisions, (3) product specifications and prices have no simultaneous effect on purchasing decisions.